Texture evolution of cold rolled and reversion annealed metastable austenitic CrMnNi steels. Issue 1 (April 2015) - Weidner, A; Fischer, K; Segel, C; Schreiber, G; Biermann, H
Abstract: A thermo-mechanical process consisting of cold rolling and subsequent reversion annealing was applied to high-alloy metastable austenitic CrMnNi steels with different nickel contents. As a result of the reversion annealing ultrafine grained material with a grain size in the range between 500 nm up to 4 μm were obtained improving the strength behavior of the material. The evolution of the texture of both the cold rolled states and the reversion-annealed states was studied either by X-ray diffraction or by EBSD measurements. The nickel content has a significant influence on the austenite stability and consequently also on the amount of the martensitic phase transformation. However, the developed textures in both steel variants with different austenite stability revealed the same behavior. In both investigated steels the texture of the reverted austenite is a pronounced Bs-type texture as developed also for the deformed austenite